Combination of ADAM17 knockdown with eplerenone is more effective than single therapy in ameliorating diabetic cardiomyopathy - Xie, Lin; Zang, Dejin; Yang, Jianmin; Xue, Fei; Sui, Wenhai; Zhang, Yun (Frontiers in Pharmacology, 2024)
Background: The renin-angiotensin-aldosterone system (RAAS) members, especially Ang II and aldosterone, play key roles in the pathogenesis of diabetic cardiomyopathy (DCM). Angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers combined with aldosterone receptor antagonists (mineralocorticoid receptor antagonists) have substantially improved clinical outcomes in patients with DCM. However, the use of the combination has been limited due to its high risk of inducing hyperkalemia. Methods: Type 1 diabetes was induced in 8-week-old male C57BL/6J mice by intraperitoneal injection of streptozotocin at a dose of 55mg/kg for 5 consecutive days. Adeno-associated virus 9-mediated short-hairpin RNA (shRNA) was used to knock down the expression of ADAM17 in mice hearts. Eplerenone was administered via gavage at 200 mg/kg daily for 4 weeks. Primary cardiac fibroblasts were exposed to high glucose (HG) in vitro for 24 h to examine the cardiac fibroblasts to myofibroblasts transformation (CMT). Results: Cardiac collagen deposition and CMT increased in diabetic mice, leading to cardiac fibrosis and dysfunction. In addition, ADAM17 expression and activity increased in the hearts of diabetic mice. ADAM17 inhibition and eplerenone treatment both improved diabetes-induced cardiac fibrosis, cardiac hypertrophy and cardiac dysfunction, ADAM17 deficiency combined with eplerenone further reduced the effects of cardiac fibrosis, cardiac hypertrophy and cardiac dysfunction compared with single therapy in vivo. High-glucose stimulation promotes CMT in vitro and leads to increased ADAM17 expression and activity. ADAM17 knockdown and eplerenone pretreatment can reduce the CMT of fibroblasts that is induced by high glucose levels by inhibiting TGFβ1/Smad3 activation; the combination of the two can further reduce CMT compared with single therapy in vitro. Conclusion: Our findings indicated that ADAM17 knockout could improve diabetes-induced cardiac dysfunction and remodeling through the inhibition of RAAS overactivation when combined with eplerenone treatment, which reduced TGF-β1/Smad3 pathway activation-mediated CMT. The combined intervention of ADAM17 deficiency and eplerenone therapy provided additional cardiac protection compared with a single therapy alone without disturbing potassium level. Therefore, the combination of ADAM17 inhibition and eplerenone is a potential therapeutic strategy for human DCM.